2016
DOI: 10.1177/0272431615609155
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Disordered Eating Behaviors in Minority Girls

Abstract: This study investigated the direct and indirect effects of biological, psychological, and sociocultural factors in predicting disordered eating behaviors in girls with overweight/obesity. A total of 135 Hispanic and African American girls (X age = 11.13 ± 1.54 years) completed surveys assessing the desire to be thinner, peer weight-related teasing, disordered eating behaviors, and demographic characteristics. Percent body fat was assessed. Structural equation modeling was conducted to examine the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…In addition, weight-related teasing, as expected, was negatively associated with appearance esteem, which supports the importance of the influence of significant others' values on body image (Ata et al, 2007). This finding is also consistent with previous suggestions that this type of comment in adolescence is associated with objectified body consciousness and eating disorders over time (Olvera et al, 2016).…”
Section: Appearance Esteem Trajectorysupporting
confidence: 90%
“…In addition, weight-related teasing, as expected, was negatively associated with appearance esteem, which supports the importance of the influence of significant others' values on body image (Ata et al, 2007). This finding is also consistent with previous suggestions that this type of comment in adolescence is associated with objectified body consciousness and eating disorders over time (Olvera et al, 2016).…”
Section: Appearance Esteem Trajectorysupporting
confidence: 90%
“…The situation of obese university students may be more prominent. To have a slim body, overweight women are more likely to perform restricted fasting or skip meals and engage in dietary restriction behaviors than their normal-weight peers [ 50 ]. A retrospective study of 179 young people aged 12–22 years in the United States found that adolescents with a history of overweight or obesity accounted for a large proportion of people who controlled their weight through dietary restrictions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%